2019
DOI: 10.1142/s0218863519500310
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Doppler broadening on cross-Kerr nonlinearity in a four-level inverted-Y system: An analytical approach

Abstract: In this work, we study the influence of Doppler broadening on cross-Kerr nonlinearity in a four-level inverted-Y atomic system under electromagnetically induced transparency (EIT) condition. The first- and third-susceptibilities in the presence of Doppler effect are derived as a function of probe, signal and coupling beams and temperature of medium. Under EIT condition, cross-Kerr nonlinearity is enhanced several orders of magnitude compared to that without EIT. The Doppler effect leads to a reduction in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Optical Kerr nonlinearities have been of tremendous interest over the last few decades because of their numerous applications in quantum optics [15][16][17][18]. Bang and his coworkers reported cross-Kerr nonlinearity (CKN) in an inverted Ytype atomic configuration [19]. A scheme for the investigation of RPD by exploiting a Sagnac interferometer in the absence of CKN was proposed, where they achieved RPD in micro-radians [20].…”
Section: Introductionmentioning
confidence: 99%
“…Optical Kerr nonlinearities have been of tremendous interest over the last few decades because of their numerous applications in quantum optics [15][16][17][18]. Bang and his coworkers reported cross-Kerr nonlinearity (CKN) in an inverted Ytype atomic configuration [19]. A scheme for the investigation of RPD by exploiting a Sagnac interferometer in the absence of CKN was proposed, where they achieved RPD in micro-radians [20].…”
Section: Introductionmentioning
confidence: 99%
“…Simplest exciting schemes of the EIT are three-level atomic systems consisting of Λ-type [5], V-type [6], and ladder-type [7] configurations. The EIT materials have interesting applications in the fields of quantum and nonlinear optics including lasing without population inversion [8], slow and fast light [9][10][11][12], enhancement of Kerr nonlinearity [13][14][15][16][17][18][19][20][21][22][23], controlling optical bistability [24][25][26][27], pulse propagation [28][29][30], all-optical switching [31,32], and so on. The studies demonstrated that the linear and nonlinear optical properties of materials are easily controlled according to the intensity, frequency, polarization, and phase of external light fields.…”
Section: Introductionmentioning
confidence: 99%